Use of Comparative Case Study Methodology for US Public Health Policy Analysis: A Review. Issue 1 (January 2017) - Dinour, Lauren M.; Kwan, Amy; Freudenberg, Nicholas
Abstract : Context: There is growing recognition that policies influence population health, highlighting the need for evidence to inform future policy development and reform. Objectives: This review describes how comparative case study methodology has been applied to public health policy research and discusses the methodology's potential to contribute to this evidence. Methods: English-language, peer-reviewed articles published between 1995 and 2012 were sought from 4 databases. Articles were included if they described comparative case studies addressing US public health policy. Two researchers independently assessed the 20 articles meeting review criteria. Main Outcome Measures: Case-related characteristics and research design tactics utilized to minimize threats to reliability and validity, such as the use of multiple sources of evidence and a case study protocol, were extracted from each article. Results: Although comparative case study methodology has been used to analyze a range of public health policies at all stages and levels, articles reported an average use of only 3.65 (out of 10) research design tactics. Conclusion: By expanding the use of accepted research design tactics, public health policy researchers can contribute to expanding the evidence needed to advance health-promoting policies. Abstract : Supplemental Digital Content is Available in the Text.